Torsional and Constrained-Axis Flexural-Torsional Buckling Tables for Steel W-Shapes in Compression - Liu, D.; Davis, Brad; Arber, L.; Sabelli, Rafael (Engineering Journal, 2013)
Torsional buckling (TB), an applicable limit state for W-shape members subject to axial compression, often controls when the torsional effective unbraced length exceeds the minor-axis flexural buckling effective unbraced length. Constrained-axis flexural-torsional buckling (CAFTB) is a potential limit state for W-shape members that are constrained to buckle with the center of twist at a location other than the centroidal axis, as is the case for a typical beam with one flange braced by a diaphragm and the other unbraced. Manual calculation of the TB or CAFTB available compressive strength is a somewhat lengthy process, especially when the section is slender for axial compression, and no design aid currently exists in the AISC Manual. This paper provides tables that facilitate the determination of TB and CAFTB available compressivestrengths. Several example calculations are also provided.